Detecting signals of chronic shedding to explain pathogen persistence: Leptospira interrogans in California sea lions. (3rd April 2017) - Buhnerkempe, Michael G.; Prager, Katherine C.; Strelioff, Christopher C.; Greig, Denise J.; Laake, Jeff L.; Melin, Sharon R.; DeLong, Robert L.; Gulland, Frances M.D.; Lloyd‐Smith, James O.
Summary: Identifying mechanisms driving pathogen persistence is a vital component of wildlife disease ecology and control. Asymptomatic, chronically infected individuals are an oft‐cited potential reservoir of infection, but demonstrations of the importance of chronic shedding to pathogen persistence at the population‐level remain scarce. Studying chronic shedding using commonly collected disease data is hampered by numerous challenges, including short‐term surveillance that focuses on single epidemics and acutely ill individuals, the subtle dynamical influence of chronic shedding relative to more obvious epidemic drivers, and poor ability to differentiate between the effects of population prevalence of chronic shedding vs. intensity and duration of chronic shedding in individuals. We use chronic shedding of Leptospira interrogans serovar Pomona in California sea lions ( Zalophus californianus ) as a case study to illustrate how these challenges can be addressed. Using leptospirosis‐induced strands as a measure of disease incidence, we fit models with and without chronic shedding, and with different seasonal drivers, to determine the time‐scale over which chronic shedding is detectable and the interactions between chronic shedding and seasonal drivers needed to explain persistence and outbreak patterns. Chronic shedding can enable persistence of L. interrogans within the sea lion population. However, the importance of chronic shedding was only apparent when surveillance data included at least two outbreaks and the intervening inter‐epidemic trough during which fadeout of transmission was most likely. Seasonal transmission, as opposed to seasonal recruitment of susceptibles, was the dominant driver of seasonality in this system, and both seasonal factors had limited impact on long‐term pathogen persistence. We show that the temporal extent of surveillance data can have a dramatic impact on inferences about population processes, where the failure to identify both short‐ and long‐term ecological drivers can have cascading impacts on understanding higher order ecological phenomena, such as pathogen persistence. Abstract : Chronic shedding of a pathogen by individuals is an oft‐cited but poorly understood mechanism for pathogen persistence due to difficulties in observing chronic shedders in many disease surveillance programmes. The authors show that the effect of chronic shedding is quantifiable when accounting for surveillance duration and interactions with short‐term epidemic drivers.